1991
DOI: 10.1109/51.70042
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuges for studying the effects of sustained acceleration on human physiology

Abstract: The operation, development, and use of high-performance centrifuges with high G-onset rates, similar to those found in modern fighter aircraft, are discussed. Their performance characteristics are examined, and the USAFSAM centrifuge at Brooks AFB in Texas is then described. Centrifuges for space research and large-radius track centrifuges are considered. The benefits of the latter are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…This reduces the load on the cardiovascular system to perfuse blood to the head. Studies have shown that leaning the seat backwards can slightly increase G-tolerance [31,49]. According to such research, seat backrest angles ranging from 13 deg to 30 deg are implemented in fighter aircraft such as the F-35 and F-16 [50].…”
Section: Hcs Configurational Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the load on the cardiovascular system to perfuse blood to the head. Studies have shown that leaning the seat backwards can slightly increase G-tolerance [31,49]. According to such research, seat backrest angles ranging from 13 deg to 30 deg are implemented in fighter aircraft such as the F-35 and F-16 [50].…”
Section: Hcs Configurational Designmentioning
confidence: 99%
“…The majority of HCSs in operation globally have three Degrees of Freedom (DoFs), which include arm rotation, gondola roll rotation, and gondola pitch rotation. Research has primarily focused on the performance improvement of three-DoF HCSs [14,23,[26][27][28][29][30][31]. However, research has concluded that HCSs with gondola roll, pitch, and yaw rotation can simulate aircraft motion more accurately and further reduce undesirable effects [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Since, for very large diameter systems, we cannot use the classical system of arms with a central motor, we need to think of a track-type system. Such a system was proposed in the early nineties by Burton et al but only for a 30 m diameter track and mainly focused on military applications (Burton et al 1991). Thirty two years before that a 152 m radius circular track system was proposed as part of a human launch simulator by NASA Marshall Space Flight Center (Gerathewohl 1961).…”
Section: Meter Track (Circumference Of 942 Meter)mentioning
confidence: 99%
“…To overcome this problem and improve pilot tolerance of G-forces, laboratories have been built as safe environment for testing pilot tolerance, i.e. a centrifuge is used to improve pilot tolerance of G-loads, simulate the high-speed manoeuvres and study the inertia of major biological systems and body physiological limits [1,2]. Variable displacement hydraulic motors (VDHMs) and hydraulic oscillators are the driven devices that are utilized to rotate the centrifuge and gondola.…”
Section: Introductionmentioning
confidence: 99%